Analisis Maslahah terhadap Ratio Decidenci Hakim dalam Memutus Perkara Dispensasi Nikah - yolanda, debita (Al-Hukkam: Journal of Islamic Family Law, 2023)
Islam does not recognize the dispensation of marriage, but there are conditions for reaching puberty in marriage. However, Article 7 (1) of Law No. 16 of 2019 concerning marriage reads: "Marriage is only permitted if a man and a woman have reached the age of 19 (nineteen) years." Based on data from the Religious Courts, in 2022 there were 215 requests for dispensation from marriage, but not all of them were granted. There are 2 decisions that have the same circumstances, namely that the prospective wife is less than 19 years old and not pregnant, but are decided with a different decision. The research used is normative legal research with a descriptive qualitative approach. The data source used is primary obtained from Law No. 16 of 2019 concerning marriage dispensation, the decisions of the Kajen Religious Court Number 242/Pdt.P/2022/PA.Kjn and Number 280/Pdt.P/2022/PA.Kjn, and secondary legal sources obtained from scientific works, scientific journals/articles, and the like. Then they were analyzed by means of reduction, presentation of data, and drawing of conclusions. The results of this study were that the two cases were decided differently because in one of the cases, which was not granted, the prospective wife was still 14 years old and had not completed her 12 year study obligation, and there was no very urgent reason. The benefit of this decision is to prevent divorce if the marriage continues, while the harm is feared to be adultery. In the case that was granted because the two of them had been in a relationship for a long time and had completed their study obligations, it was feared that adultery would occur. The benefit of this decision is to avoid adultery and harm. It is feared that both of them are not mentally ready.